Local Wisdom-Based Character Education in the Sundanese Family Environment: A Study of the Cireundeu Indigenous Community in Cimahi City - Wawan Hermawan; Mukmin Mugni Sehabudin; Revita Yanuarsari (Attractive : Innovative Education Journal, 2026)
This study aims to describe the Sundanese local wisdom values instilled within the family environment, the role of families in character education, the process of character internalization through cultural activities, and the challenges faced in its implementation within the Cireundeu Indigenous Community of Cimahi City. The study employed a qualitative approach using a case study method. Research participants consisted of traditional leaders, parents, children/adolescents, and community leaders selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation studies. Data analysis employed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that character education within the Cireundeu Indigenous Community is implemented through the internalization of Sundanese local wisdom values such as silih asih (mutual affection), silih asah (mutual learning), silih asuh (mutual guidance), sabilulungan (mutual cooperation), courtesy, responsibility, simplicity, and gratitude. Families function as educators, role models, motivators, and supervisors in shaping children's character. The internalization of character values is strengthened through children's participation in cultural and social activities within the indigenous community. The resulting character traits include politeness, responsibility, social concern, independence, simplicity, and appreciation of local culture. Despite challenges posed by digital technology, social media, and cultural globalization, the Cireundeu community has successfully maintained its cultural values through the philosophy of Ngindung ka Waktu, Mibapa ka Jaman, which emphasizes adapting to changing times without losing cultural identity. This study concludes that character education based on Sundanese local wisdom within the family environment serves as an effective model for shaping the character of younger generations while preserving local cultural sustainability.